Prevention of breast cancer with the breast self-examination method (BSE) in the Negeri Lima village, Leihitu District, Maluku Province - Theopilus Wilhelmus Watuguly; Fredy Leiwakabessy; Johanis Fritzgal Rehena; Windi Mose; Syahran Wael (BIOEDUPAT: Pattimura Journal of Biology and Learning, 2022)
The number of incidences and deaths from cancer is increasing every year around the world. However, currently available cancer treatment methods still have weaknesses, the discovery of cancer drugs is still very important. The purpose of this study was to determine the effect of the level of public knowledge about breast cancer with BSE behavior on housewives in Negeri Lima Village, Maluku Province. The design of this research is descriptive analytic with a cross-sectional approach. The study was conducted in May 2022. The population in this study were residents of the village of Negeri Lima. Sampling using the method with 50 respondents. The tool used in this research is a questionnaire. The analysis technique used is Chi Square analysis. The results showed that the influence of the level of knowledge about breast cancer on housewives was mostly in the good category of 60.5%. BSE behavior in housewives is mostly in the category of not doing BSE by 40%. The results of the Chi Square analysis obtained the calculated X2 value of 55.40 with a p value of 0.000 (p <0.05). The close relationship between the level of knowledge of breast cancer with conscious behavior has a strong category indicated by a coefficient of 0.50. The conclusion of this study is that there is a relationship between the level of knowledge of mothers about breast cancer and the BSE behavior.